Penerapan Pencatatan Akuntansi Berdasarkan SAK EMKM (Studi Kasus UMKM Kripik Kulit Ikan Patin) - Islamiati, Nanda Elfrida; Nuraini, Fitri; Soedjono, Soedjono (Fakultas Ekonomi Prodi Akuntansi, 2023)
Micro, small and medium enterprises (MSMEs) are one of the economic sector businesses that have an important role in advancing the economy in Indonesia. As a business operating in the MSME economic sector, of course it cannot be separated from the activities of preparing financial reports. However, in practice there are still many MSME players who have not prepared financial reports in accordance with Financial Accounting Standards. The purpose of this research is to find out how to prepare financial reports for the